Synoviolin alleviates GSDMD‐mediated periodontitis by suppressing its stability - Ying Pang; Lili Liu; Shuainan Wu; Jianqi Wang; Lu Liu (Immunity, Inflammation and Disease, 2023)
Abstract Introduction Inflammasome and pyroptosis play important roles in periodontitis. Gasdermin D (GSDMD), a key factor in pyroptosis, is cleaved by caspase‐1 and regulated by ubiquitination. Synoviolin is a ubiquitin E3 ligase that interacts with GSDMD. In this study, the effects of Synoviolin on inflammasome activation and periodontitis were explored. Methods The expression of IL‐1β, GSDMD, and Synoviolin in peripheral blood mononuclear cells from patients with periodontitis was determined. The interaction between GSDMD and Synoviolin was studied. The cytokine level in gingival tissues and the distance from the cementoenamel junction to the alveolar bone crest were measured in mice with Synoviolin deficiency in myeloid cells. Results We reported that elevated mRNA and protein levels of IL‐1β and GSDMD, decreased levels of Synoviolin mRNA and protein, and decreased ubiquitination of GSDMD were associated with periodontitis. Synoviolin interacted with GSDMD. Synoviolin‐deficient bone marrow‐derived macrophages had increased IL‐1β and IL‐18 secretion after ATP stimulation. Mice with Synoviolin deficiency in myeloid cells had more severe periodontitis and upregulated IL‐1β and IL‐18. Conclusions Therefore, we conclude that Synoviolin suppresses inflammasome activation and periodontitis by regulating GSDMD stability.